1996
DOI: 10.1212/wnl.47.1.83
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of nonconvulsive seizures in the intensive care unit using continuous EEG monitoring

Abstract: Of 49 patients with nonconvulsive seizures studied with continuous EEG monitoring, the overall mortality was 33% (16/49). Of the 23 patients with nonconvulsive status epilepticus (NCSE), 13 died (mortality 57%). Individual variables significantly associated with mortality were age, presence of NCSE, seizure duration, hospital and NICU length of stay, and delay to diagnosis and etiology (acute illness versus remote symptomatic). With multivariate logistic regression, only seizure duration (p = 0.0057, OR = 1.13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
436
4
21

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 628 publications
(478 citation statements)
references
References 13 publications
17
436
4
21
Order By: Relevance
“…The incidence of NCS in this model is 81%, the mean number of NCS/animal is 10.6 over a 2 hour observation period, and the mean duration of each episode is 60 sec (Hartings et al, 2003b). The occurrence and duration of NCS in brain injured patients are critical determinants of outcome and mortality (Jordan, 1995;Litt et al, 1998;Young et al, 1996). Although electric seizures and acute brain injury work synergistically to worsen outcome, the underlying pathomechanism is still unclear.…”
Section: Discussionmentioning
confidence: 92%
“…The incidence of NCS in this model is 81%, the mean number of NCS/animal is 10.6 over a 2 hour observation period, and the mean duration of each episode is 60 sec (Hartings et al, 2003b). The occurrence and duration of NCS in brain injured patients are critical determinants of outcome and mortality (Jordan, 1995;Litt et al, 1998;Young et al, 1996). Although electric seizures and acute brain injury work synergistically to worsen outcome, the underlying pathomechanism is still unclear.…”
Section: Discussionmentioning
confidence: 92%
“…Even so, in some cases, excessive and overly aggressive treatment of seizures has also been reported to result in worsening of outcomes. 10 Several studies in animals have clearly shown the importance of treating non-convulsive seizures, which may be associated with increased metabolic, oxidative, and excitotoxic stress on brain at-risk, [13][14][15] and thus may result in irreversible neuronal injury. The management of NCSE is less clear in patients in whom NCSE presents as a manifestation of a serious underlying illness.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of NCS and NCSE ranges between 8 and 48% depending on the patient population studied [1][2][3][4][5][6][7][8]. The mortality rate of neurologically critically ill patients afflicted with NCSE is 18-57% [9,10] while the presence of NCS is associated with a mortality rate of 33% [10]. Although the presence of NCS does not independently affect mortality, it has been found that the duration of NCS is associated with an increase in mortality [10] and that increasing seizure burden worsens cognitive and functional outcomes [11].…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate of neurologically critically ill patients afflicted with NCSE is 18-57% [9,10] while the presence of NCS is associated with a mortality rate of 33% [10]. Although the presence of NCS does not independently affect mortality, it has been found that the duration of NCS is associated with an increase in mortality [10] and that increasing seizure burden worsens cognitive and functional outcomes [11]. Therefore, prompt identification and appropriate treatment are essential, requiring CCEEG monitoring since seizures are nonconvulsive in 92% of critically ill patients whose hospital course is complicated by NCS or NCSE [1].…”
Section: Introductionmentioning
confidence: 99%